LOCAL POTENTIAL-BASED COMMUNITY EMPOWERMENT STRATEGY THROUGH THE BREEDING GARDEN TOUR VILLAGE PROGRAM AT KABUPATEN KEDIRI - Isnaini, Rizqi Nur; Yuliati, Nanik; Ariefianto, Lutfi (Universitas Pendidikan Indonesia (UPI), 2022)
The development of tourism destinations in Indonesia is a development that is intensively carried out by the central government and local governments. A characteristic of a tourist village has the concept of a form of integration between attractions, accommodation, and fulfillment of facilities in a community structure that is integrated with traditions and procedures that already apply. The planning of the empowerment strategy must be designed in such a way as to form a structured community organization. The development of tourist villages in Jambu Village has the main goal of building local communities to have cultural and economic resilience. With adequate economic support, the people of Jambu Village will be able to maintain and develop their cultural heritage or natural potential. Thus, in the development of tourist villages, the goals and targets are to provide opportunities or encourage the community to be more active, creative, and pro-active in developing and managing tourist attractions in their area. The purpose of this study was to determine the strategy of community empowerment based on local potential through the village tourism program for the Seedling Gardens in Kediri Regency. Determination of the place in the study that is using a purposive area, because the selection of the place is based on certain considerations. The technique of determining the informants in this study used snowball sampling. Data collection techniques using the method of observation, interviews and documentation. Techniques for checking the validity of the data used extended participation, persistence of observation, and triangulation. The triangulation used is technique triangulation and source triangulation. Data analysis using Miles and Huberman includes: data collection, data reduction, data presentation and data verification. The results of this study indicate that there is a community empowerment strategy carried out by residents around Jambu Village to improve the standard of living of the local community. There are several things that are done to achieve success according to the plan. There are 3 developments in forming an empowerment strategy, namely human development which includes recruitment, training, and education. Community development is related to the application of Sapta Pesona and environmental revitalization. As well as institutional development in the form of a BUMDes organization to oversee tourism villages. Suggestions for further writers are expected to be able to explore the topic of increasing empowerment strategies related to increasing the existence of a community organization that develops tourism based on local potential.